Water supply sanitation and hygiene in populated areas: tutorial for students studying in the medical specialityГигиена водоснабжения населённых мест: учебное пособие для студентов - Кавешников, В. С. кардиология 19750627 Владимир Сергеевич (Издательство СибГМУ, 2022)
The tutorial is prepared in accordance with the Federal State Educational Standard of Higher Professional Education, for students studying in the medical specialty. The textbook is based on the publication in Russian "Guide to Practical Training on Hygiene". The tutorial has been revised and supplemented. The tutorial highlights the hygienic principles of water supply of populated areas. In presenting the material, the current regulatory documents - State Standards and SanPiNs were used.